Sensitivity analysis of frequency and voltage stability in islanded microgrid - Laaksonen, Hannu; Kauhaniemi, Kimmo (CIRED, 2007)
This paper studies the voltage and frequency stability of an islanded microgrid and the sensitivity of these quantities to certain changes in system configuration. In conventional power systems the system frequency is coupled with the rotor speed of the directly grid connected large synchronous generators and power unbalance can be seen as changed system frequency. But in an islanded microgrid it is possible that all generation units are connected to grid via converters and there is no inertia of rotating masses to affect the frequency. In that case the frequency has to be created by a power electronic device and the frequency is more of less fixed and power unbalance cannot be detected in the classical way. The studied urban low voltage (LV) network based microgrid consists of three converters and one synchronous generator based distributed generation (DG) units. The studies are made with PSCAD simulation software.
Keywords: electrical power networks; distribution of electricity; electric power; voltage; frequency changers; electric machines; diesel engines; generators (devices); optimisation; parallel publishing; fi=Sähkötekniikka|en=Electrical Engineering|